Prevalence of Methicillin-ResistantStaphylococcus aureus and Multidrug-Resistant Strains from Patients Attending the Referral Hospitals of Amhara Regional State, Ethiopia - Moges, Feleke; Tamiru, Tadele; Amare, Azanaw; Mengistu, Getachew; Eshetie, Setegn; Dagnew, Mulat; Feleke, Tigist; Gizachew, Mucheye; Abebe, Wondwossen (International Journal of Microbiology, 2023)
Background. Staphylococcus aureus (S. aureus) causes different types of human infections and can develop resistance to many antibiotics. There is a scarcity of data on the mecA gene and multidrug-resistant (MDR) strain distribution of this organism in developing countries, such as Ethiopia. This study investigated the presence of mecA gene and MDR profile of S. aureus among patients attending referral hospitals of Amhara regional state. Methods. Of the total of 110 isolates collected from Amhara regional referral hospitals, 70 MDR isolates were further processed for isolation of S. aureus mecA gene. Genomic DNA was isolated using a Sigma-Aldrich genomic DNA isolation kit for Gram-positive bacteria. Amplification of S. aureus mecA gene was performed with the amplicon size of 533 bp. Antimicrobial susceptibility test including methicillin resistance was determined by the Kirby–Bauer disc diffusion method. Results. The majority of the isolates were recovered from patients aged less than 5 years (51; 36.7%) and the least number of isolates was recorded in age group greater than 60 years (6; 4.3%). Most of the isolates were from blood (61; 43.9%), followed by wounds (45; 32.4%). A high resistance rate was observed in penicillin (81; 73.6%), followed by cotrimoxazole (78; 70.9%), ceftriaxone (76; 69%), erythromycin (66; 60%), and tetracycline (65; 59.1%). Phenotypically, considering cefoxitin as a surrogate marker, 38 (34.5%) of the isolates were methicillin-resistant. The overall MDR isolates were 80 (72.7%). The PCR amplification result of the mecA gene was 14 (20%). Conclusions and Recommendations. High rates of MDR and methicillin-resistantS. aureus were reported. PCR amplification indicated that 20% of MRSA isolates were the mecA gene carriers. Large-scale studies for the detection of MDR strains of S. aureus including MRSA using molecular techniques should be encouraged in the Amhara region.